1989
DOI: 10.1104/pp.90.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Pod Development in Oilseed Rape (Brassica napus)

Abstract: The endogenous levels of several plant growth substances (indole acetic acid, IAA; abscisic acid, ABA; zeatin, Z; zeatin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Another factor which affects the evapotranspirational demands of plants may be the number of individual B. napus plants per unit area, which is due to the high compensation ability of plants (Diepenbrock and Becker, 1995) (Figure 1), even if the PAR and VPD values were the same before as well as after the BBCH 81-83 stages. This indirectly supports the results of phytohormone growth in the siliqua (pods) and the following photosynthesis inhibition (Bouille et al, 1989;Hauser et al, 1990). Singal et al (1995) proved photosynthesis intensity decline in the siliqua of Brassica campestris L. plants as dependent on the senescence process.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…Another factor which affects the evapotranspirational demands of plants may be the number of individual B. napus plants per unit area, which is due to the high compensation ability of plants (Diepenbrock and Becker, 1995) (Figure 1), even if the PAR and VPD values were the same before as well as after the BBCH 81-83 stages. This indirectly supports the results of phytohormone growth in the siliqua (pods) and the following photosynthesis inhibition (Bouille et al, 1989;Hauser et al, 1990). Singal et al (1995) proved photosynthesis intensity decline in the siliqua of Brassica campestris L. plants as dependent on the senescence process.…”
Section: Methodssupporting
confidence: 59%
“…The pods undergo photosynthesis after the flowering phase (Singal et al, 1995). Successive physiological processes associated with the senescence process of the plant, which are, for example, displayed by changes in the hormonal level in the pods (Bouille et al, 1989), affect the decrease in the activities of photosynthetic and water consumption (Hauser et al, 1990). The transpiration values of an individual plant and their conversion to the whole stand are relatively well documented in trees (Schulze et al, 1985;Č ermák et al, 1995, etc.).…”
Section: Introductionmentioning
confidence: 97%
“…Drought stress during the reproductive growth stages creates a hormone imbalance that inhibits pod formation and seed development, causing Brassica species to drop damaged flowers and focus energy into younger flowers (Canola Watch, 2016). Drought stress during reproductive development reduces levels of hormones (cytokinins and auxins) that prevent flower and pod abortion, resulting in hormonal imbalances within the plant (de Bouille et al, 1989). Although both locations recorded temperatures higher than 25°C during the critical growth stages, temperatures were elevated for a longer period, and moisture conditions were less favorable at Pierre in both years.…”
Section: Resultsmentioning
confidence: 99%
“…Since pod length was closely associated with the number of seeds from very early on, and a higher cell division in chlorenchyma and parenchyma of the pod wall was found in the presence of seeds, it is reasonable to assume that seeds initially produce cytokinin-like substances that induce cell division. Studies in winter rape showed that concentrations of cytokinins (zeatin and zeatin riboside) reached peak levels on the third 10 100 day, when pods were c. 10 mm in length (de Bouille et al 1989). A major peak in cytokinin concentration of lupin seeds was shown to coincide with the stage of cell division in the fruit wall (Readman 1983).…”
Section: Seed Number and Development Of The Pod Wall {Expt 1)mentioning
confidence: 99%